ANALISIS SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS DARI PENJUALAN TUNAI GUNA MENINGKATKAN PENGENDALIAN INTERNAL (Studi Kasus CV. Davion Kecamatan Alok Barat Kabupaten Sikka) - Sunga, Maria Faustin Silvana; Dince, Maria Nona; Lamawitak , Paulus Libu (Universitas Nusa Nipa Maumere, 2025)
This study aims to analyze the accounting information system for cash receipts from cash sales, focusing on improving internal control at CV Davion. Employing a qualitative descriptive method, data was gathered through interviews, observations, and documentation. The findings indicate that the current accounting information system has several weaknesses, particularly concerning the segregation of duties. Overlapping responsibilities, reliance on manual processes, and the lack of formalized issues, it is essential to implement improvements such as organizational restructuring, clear segregation of roles, the adoption of a computererized system, and the introduction of systematically documented procedures. These enhancements are anticipated to strengthen the company’s internal control. Increase the reliability of financial information, streamline operational activivities, and facilitate more effeective managerial decision-making. Furthermore, the results of this study are expected to aid the company in developing a more robust internal control system and to serve as a reference for future research.